[PP.11.13] PULSE PRESSURE AMPLIFICATION IN PATIENTS WITH AORTIC COARCTATION AFTER AORTIC ARCH REPAIR. (September 2016) - Murakami, T.; Nawa, T.; Shiraishi, M.; Takeda, A.
Abstract : Objective: One of the important problems in patients with aortic coarctation after aortic arch repair is a future cardiovascular disease. We previously reported that a new pressure wave reflection (PWR) occurred from the surgically repaired site. In normal aorta, the pulse pressure (PP) in descending aorta (DAo) is larger than that in ascending aorta (AAo), because the major PWR occurs around the aortic bifurcation (pulse pressure amplification). If the repaired site generates the new PWR, PP in AAo is enhanced and it could cause the future cardiovascular disease. Design and method: Sixteen patients after aortic arch repair without pressure gradient at the repaired site were enrolled. A pressure sensor mounted catheter recorded pressure waveforms in AAo and DAo. The pressures were compared with those of age-matched patients with a normal aortic arch. Results: The patient's age was 7.9 ± 4.2 years and they underwent the aortic arch repair at 0.08 ± 0.08 years. The systolic blood pressure was 106.1 ± 12.7 mmHg at AAo and 109.3 ± 13.7 mmHg at DAo. The PP was 38.7 ± 12.8 mmHg at AAo and 38.4 mmHg at DAo. The difference of PP between DAo and AAo (PP at DAo – PP at AAo) was −0.25 ± 1.7 mmHg. In the control subjects, the PP at AAo was 35.3 mmHg at AAo and 40.4 mmHg at DAo. The difference of PP between DAo and AAo in control subjects was 5.1 ± 2.8 mmHg. The difference of PP between DAo and AAo in the arch repaired patients was significantly lower than that in the control subjects (t = 7.426, p < 0.0001). Conclusions: Pulse pressure amplification in AAo is augmented in patients with aortic coarctation after aortic arch repair and it could cause the future cardiovascular disease.